Honey-loaded natural rubber dressing for treatment of atopic dermatitis: A physicochemical, antioxidant, in vitro and in vivo characterization - Forster, Samuel; Farhadi, Neda; Lopes Filho, Paulo Eduardo de Lima [UNESP]; Piazza, Rodolfo Debone [UNESP]; Costa-Marques, Rodrigo Fernando [UNESP]; Tanaka, Jean Lucas [UNESP]; Scontri, Mateus [UNESP]; Dos Santos, Lindomar Soares; Cai, Yi; Cao, Wei; Guerra, Nayrim Brizuela [UNESP]; Burd, Betina Sayeg [UNESP]; et al. (Elsevier, 2025)
Atopic dermatitis, or eczema, is a chronic autoimmune disease that affects 223 million people worldwide. Honey is used to treat eczema due to its emollient, antioxidant, and anti-inflammatory properties when applied topically. However, its stickiness can negatively impact patient compliance with treatment. In this study, we incorporated Brazilian multifloral honey into natural rubber latex (NRL) dressings to reduce its adhesive properties. Fourier transform infrared spectroscopy demonstrated that honey was weakly bound to NRL. Stereoscopic images revealed homogeneous surfaces without pores for both dressings, while atomic force microscope images showed an increase in roughness after honey incorporation. Additionally, wettability, thermogravimetry/derivative thermogravimetric analysis, and mechanical testing analyses exhibited significant changes following honey incorporation. Furthermore, kinetic studies indicated that NRL released honey, displaying an initial burst release followed by a plateau, consistent with a physisorption interaction between honey and NRL. Excellent cytocompatibility (>99 % viability) of human dermal fibroblasts after exposure to Honey-NRL was confirmed by metabolic activity and live/dead assays. Antioxidant activity (AA) analysis validated that honey at 25 % concentration completely scavenged the free radical signal in the electron paramagnetic resonance spectra. Moreover, we observed that NRL incorporated with honey maintained an AA of 100 %, preserving honey's phytochemical properties. Lastly, the safety of these dressings was evaluated using the Galleria mellonella model. Larvae inoculated with Honey-NRL maintained a 100 % survival rate, demonstrating that Honey-NRL is biocompatible and may serve as an alternative treatment for eczema. In summary, our results suggest that these dressings are safe, effective (as honey's AA was preserved), cost-effective, and suitable for daily application (every 24 h).